The Merovingians in historiographical tradition from the sixth to the sixteenth centuries - Foḳs, Yaniv 1975- (Cambridge University Press, 2023)
The Merovingian centuries were a foundational period in the historical consciousness of western Europe, and their stories were shaped through a process of historiographical adaptation across a millennium. This expert commentary is for scholars interested in early medieval history and historiography.